MENUMBUHKAN TOLERANSI DALAM PEMBANGUNAN EKONOMI UNTUK MENCAPAI PERDAMAIAN UNIVERSAL - Shifa Alfiah Fajriah; Silvi Aulia; Suryadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study examines the role of tolerance in economic development and universal peace. Data collection was conducted through a literature review, which included reading and analyzing literature on legal regulations, police profiles, and relevant journals. The results show that tolerance is crucial for accepting and respecting differences in society, which in turn enhances cooperation, productivity, and reduces social conflicts. Religious tolerance is also found to have a positive impact on the economic development of a region. Additionally, tolerance improves access to education and healthcare, and strengthens international and global humanitarian cooperation. Sustainable and tolerance-based economic development can help reduce conflicts and inequalities, as well as increase public awareness of the importance of peace. This study suggests that governments and society work together to enhance tolerance and equality in various fields, including economics, education, and social policy. By doing so, it is hoped that a more harmonious and peaceful society will be created, along with sustainable development and universal peace. Keywords: Tolerance, Economic Development, Universal Peace